PENGARUH PENCAMPURAN LIMBAH SAYUR KUBIS (Brasica oleracea) PADA MEDIA FESES BABI TERHADAP PRODUKTIVITAS CACING TANAH (Lumbricus rubellus) - Tunggul Ferry Sitorus (Universitas Muara Bungo, 2023)
Research with the title effect of mixing cabbage waste (Brasica oleracea) in pig feces media on the productivity of earthworms (Lumbricus rubellus). From November 2022 to December 2022 on Jln. Pelita I. No 37e, West Sidorame II, Medan Perjuangan, Medan City, North Sumatra. This study aims to determine the effect of mixing cabbage waste on cocoon production, increasing the number of earthworm tillers and increasing earthworm biomass. This research was conducted for 43 days. This study used a completely randomized design with 5 treatments and 6 replications, namely P0 (0% cabbage waste in pig feces media), P1 (10% cabbage waste in pig feces media), P2 (20% cabbage waste in pig feces media), P3 (30% cabbage waste in pig feces media) and P4 (40% cabbage waste in pig feces media). The data obtained in this study will then be analyzed for variance (ANOVA) and then proceed with the DMRT test or Duncan's test and the Least Significant Difference (LSD) test. From this study it can be concluded that mixing cabbage waste in pig feces media has a very significant effect (P0.01) on cocoon production, increasing the number of earthworm tillers and increasing earthworm biomass. Based on the results of this study, it was found that the best administration of cabbage vegetable waste in pig feces media was at the level of 30%.